2000
DOI: 10.1007/s003300000434
|View full text |Cite
|
Sign up to set email alerts
|

Absolute renal blood flow quantification by dynamic MRI and Gd-DTPA

Abstract: The aim of this study was to demonstrate the feasibility of the absolute renal blood flow quantification using MRI and injection of contrast media. Using a T1-weighted fast gradient sequence following an intravenous bolus injection of Gd-DTPA, dynamic images of the kidney were obtained in patients with well-functioning native kidneys (n = 7) or transplant (n = 9), with significant renal artery stenosis (n = 4) and with renal failure (n = 7). After signal intensity calibration, the absolute renal perfusion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 25 publications
5
60
0
5
Order By: Relevance
“…Fast acquisition techniques allow suffi cient temporal resolution to monitor intra-renal signal changes during fi rst pass of the agent. Approaches have been described [43] enabling quantifi cation of absolute cortical and medullary perfusion. Th is would make gadoliniumbased MRI technology of great interest for the assessment of renal perfusion.…”
Section: Contrast-enhanced Mri Mod Alitiesmentioning
confidence: 99%
“…Fast acquisition techniques allow suffi cient temporal resolution to monitor intra-renal signal changes during fi rst pass of the agent. Approaches have been described [43] enabling quantifi cation of absolute cortical and medullary perfusion. Th is would make gadoliniumbased MRI technology of great interest for the assessment of renal perfusion.…”
Section: Contrast-enhanced Mri Mod Alitiesmentioning
confidence: 99%
“…7) (62,(64)(65)(66)(67)(68)(69)(70)(71)(72). To data there are only a few clinical studies measuring renal perfusion.…”
Section: Functional Mr Imaging Of the Kidneysmentioning
confidence: 99%
“…Fundamental work was published by Dujardin et al who demonstrated age-related changes in renal perfusion in men, but only little change in women (73). Clinical applications have so far mainly focused on patients with renal artery stenosis in whom two studies found significantly decreased renal perfusion parameters associated with significant renal artery stenosis (64,65). They reported a mean blood flow of 2.54 mL/ min/g tissue for healthy patients, with this value dropping to 1.09 mL/min/g tissue for patients with high-grade renal artery stenosis.…”
Section: Functional Mr Imaging Of the Kidneysmentioning
confidence: 99%
“…[1], T 1 may also be calculated using Eq. [3], which does not require knowledge of the exact flip angle. To ensure that B 1 inhomogeneities do not degrade the accuracy of the thus obtained T 1 values, it was shown by Deichmann and Haase (10) that a low flip angle of less than 10°has to be used for the SFL sequence.…”
Section: T 1 Calculationmentioning
confidence: 99%
“…CA concentrations are commonly deduced from relative signal changes in dynamically acquired MR images. However, CA concentration-time curves obtained this way are prone to errors due to nonlinear signal behavior or tissue-specific influences (2), if no signal calibration is performed (3).…”
mentioning
confidence: 99%